2021
DOI: 10.1038/s41598-021-90291-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental morph combination does not influence innate immune function in nestlings of a colour-polymorphic African raptor

Abstract: Conditions experienced during early life can have long-term individual consequences by influencing dispersal, survival, recruitment and productivity. Resource allocation during development can have strong carry-over effects onto these key parameters and is directly determined by the quality of parental care. In the black sparrowhawk (Accipiter melanoleucus), a colour-polymorphic raptor, parental morphs influence nestling somatic growth and survival, with pairs consisting of different colour morphs (‘mixed-morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 109 publications
(165 reference statements)
0
7
0
Order By: Relevance
“…This could be due to an improved absorption of carotenoids as well as an accumulation over time and was also reported in other raptor populations (Casagrande, Costantini et al 2007 ; García-Heras, Arroyo et al 2017 ). However, no association between carotenoids and body mass was seen, which could indicate that integument coloration and blood concentration depend on the quality (carotenoid content) of the ingested prey items rather than the quantity of food, as mentioned in other studies (Eeva, Sillanpää et al 2009 ; Sternalski, Mougeot et al 2010 ; Sternalski, Mougeot et al 2012 ; Nebel, Amar et al 2021 ). This could also be one reason why no relationship between carotenoids and hatch rank was found either, because hatch rank is directly informed by nestling size and was assigned in the field.…”
Section: Discussionmentioning
confidence: 74%
“…This could be due to an improved absorption of carotenoids as well as an accumulation over time and was also reported in other raptor populations (Casagrande, Costantini et al 2007 ; García-Heras, Arroyo et al 2017 ). However, no association between carotenoids and body mass was seen, which could indicate that integument coloration and blood concentration depend on the quality (carotenoid content) of the ingested prey items rather than the quantity of food, as mentioned in other studies (Eeva, Sillanpää et al 2009 ; Sternalski, Mougeot et al 2010 ; Sternalski, Mougeot et al 2012 ; Nebel, Amar et al 2021 ). This could also be one reason why no relationship between carotenoids and hatch rank was found either, because hatch rank is directly informed by nestling size and was assigned in the field.…”
Section: Discussionmentioning
confidence: 74%
“…This finding is in accordance with other urban-dwelling avian species (see Liker et al 2008 ; Meillère et al 2015 ; Herrera-Dueñas, 2018 ; Isaksson et al, 2005 ; Chamberlain et al, 2009 ). However, a recent urban raptor study showed that offspring with lower body mass indices also had higher local apparent survival rates (Nebel et al 2021 )—unfortunately we do not have data on post-fledging survival in our population from which to infer potential long-term fitness consequences.…”
Section: Discussionmentioning
confidence: 88%
“…One would expect high‐‘quality’ nestlings to show stronger antioxidant capacity, lysis and bactericidal capacity, but curiously, none of these indices were correlated with body mass index. In a related study (Nebel et al, 2021 ), nestlings with lower body mass index showed higher survival rates—an index of energy reserves and physical well‐being. This finding raises questions about the suitability of avian body morphometrics (Green, 2001 ; Peig & Green, 2010 ) as proxies of individual condition.…”
Section: Discussionmentioning
confidence: 90%